Apersonal values view of international entrepreneurial intention - Akhtar Ammeer, Mohammad (2021)
Purpose– Recognising the shortage of research investigating the effect of individual characteristics in cross-border entrepreneurship, this study models the dimensions of personal values as predictors of international entrepreneurship. Also, noting the paucity of evidence on the influence of ethnicity and gender in the personal values and international entrepreneurship nexus, the study undertakes a multi-group analysis to clarify the moderating effects of these social antecedents in the context of Mauritius. Design/methodology/approach– Cross-sectional data from Mauritius is examined using a sample of 504 students spread across six universities. The analysis takes a structural equation modelling approach. Findings– The results show that, comparing the distinct personal values dimensions, international entrepreneurshiphasapositiveassociationwithself-enhancementandopennesstochange.Furthermore,ithas a non-significant relationship with self-transcendence and a negative connection with conservation. Also, the multi-group analyses revealed significant differences in the individual correlations across gender and ethnic categories. Originality/value– Building on emerging empirical interest in the literature, this study presents novel evidence of the link between personal values and international entrepreneurial intention in the context of Mauritius. Additionally, examining the moderating influence of ethnicity and gender in the personal values, international entrepreneurship nexus advancescurrent literature. On a practical level, the studyoffers insights to universities and other stakeholders tasked with nurturing international entrepreneurial behaviour among students to contemplate personal and social antecedents and, accordingly, adapt their entrepreneurship pedagogy.